Attenuation of fibroblast activation and fibrosis by adropin in systemic sclerosis - Liang, Minrui; Dickel, Nicholas; Györfi, Andrea Hermina; SafakTümerdem, Bilgesu; Li, Yi Nan; Rius Rigau, Aleix Rius; Liang, Chunguang; Hong, Xuezhi; Shen, Lichong; Matei, Alexandru-Emil; Trinh-Minh, Thuong; Tran-Manh, Cuong; et al. (Science Translational Medicine, 2024)
Fibrotic diseases impose a major socioeconomic challenge on modern societies and have limited treatment options. Adropin, a peptide hormone encoded by the energy homeostasis–associated (ENHO) gene, is implicated in metabolism and vascular homeostasis, but its role in the pathogenesis of fibrosis remains enigmatic. Here, we used machine learning approaches in combination with functional in vitro and in vivo experiments to characterize adropin as a potential regulator involved in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). We demonstrated consistent down-regulation of adropin/ENHO in skin across multiple cohorts of patients with SSc. The prototypical profibrotic cytokine TGFβ reduced adropin/ENHO expression in a JNK-dependent manner. Restoration of adropin signaling by therapeutic application of bioactive adropin34–76 peptides in turn inhibited TGFβ-induced fibroblast activation and fibrotic tissue remodeling in primary human dermal fibroblasts, three-dimensional full-thickness skin equivalents, mouse models of bleomycin-induced pulmonary fibrosis and sclerodermatous chronic graft-versus-host-disease (sclGvHD), and precision-cut human skin slices. Knockdown of GPR19, an adropin receptor, abrogated the antifibrotic effects of adropin in fibroblasts. RNA-seq demonstrated that the antifibrotic effects of adropin34–76 were functionally linked to deactivation of GLI1-dependent profibrotic transcriptional networks, which was experimentally confirmed in vitro, in vivo, and ex vivo using cultured human dermal fibroblasts, a sclGvHD mouse model, and precision-cut human skin slices. ChIP-seq confirmed adropin34–76-induced changes in TGFβ/GLI1 signaling. Our study characterizes the TGFβ-induced down-regulation of adropin/ENHO expression as a potential pathomechanism of SSc as a prototypical systemic fibrotic disease that unleashes uncontrolled activation of profibrotic GLI1 signaling.
CRIS-Team Scopus Importer:2024-04-05

Combination therapies of porcupine inhibition with ruxolitinib, ibrutinib, or belumosudil in murine sclerodermatous GVHD - Hong, Xuezhi; Xiao, Yanhua; Xu, Liyan; Shen, Lichong; Neelagar, Ranjana; Devakumar, Veda; Trinh-Minh, Thuong; Liang, Minrui; Rigau, Aleix Rius; Zhang, Yun; Li, Yi Nan; Dees, Clara; et al. (Blood Advances, 2025)
CRIS-Team Scopus Importer:2025-04-01

PGC-1α regulates autophagy to promote fibroblast activation and tissue fibrosis - Zhang, Yun; Shen, Lichong; Zhu, Honglin; Dreissigacker, Katja; Distler, Diana; Zhou, Xiang; Györfi, Andrea-Hermina; Bergmann, Christina; Meng, Xianyi; Dees, Clara; Trinh-Minh, Thuong; Ludolph, Ingo; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives Coactivators are a heterogeneous family of transcriptional regulators that are essential for modulation of transcriptional outcomes and fine-tune numerous cellular processes. The aim of the present study was to evaluate the role of the coactivator peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) in the pathogenesis of systemic sclerosis (SSc). Methods Expression of PGC-1α was analysed by real-time PCR, western blot and immunofluorescence. Modulation of autophagy was analysed by reporter studies by expression of autophagy-related genes. The effects of PGC-1α knockdown on collagen production and myofibroblast differentiation were analysed in cultured human fibroblasts and in two mouse models with fibroblast-specific knockout of PGC-1α. Results The expression of PGC-1α was induced in dermal fibroblasts of patients with SSc and experimental murine fibrosis. Transforming growth factor beta (TGFβ), hypoxia and epigenetic mechanisms regulate the expression of PGC-1α in fibroblasts. Knockdown of PGC-1α prevented the activation of autophagy by TGFβ and this translated into reduced fibroblast-to-myofibroblast differentiation and collagen release. Knockout of PGC-1α in fibroblasts prevented skin fibrosis induced by bleomycin and by overexpression of a constitutively active TGFβ receptor type I. Moreover, pharmacological inhibition of PGC-1α by SR18292 induced regression of pre-established, bleomycin-induced skin fibrosis. Conclusion PGC-1α is upregulated in SSc and promotes autophagy to foster TGFβ-induced fibroblast activation. Targeting of PGC-1α prevents aberrant autophagy, inhibits fibroblast activation and tissue fibrosis and may over therapeutic potential.
CRIS-Team Scopus Importer:2020-09-11
Keywords: fibroblasts; systemic sclerosis; treatment

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease - Zhang, Yun; Shen, Lichong; Dreißigacker, Katja; Zhu, Honglin; Trinh, Minh Thuong; Meng, Xianyi; Tran Manh, Cuong; Dees, Clara; Matei, Alexandru-Emil; Chen, Chih-Wei; Ditschkowski, Markus; Krauss, Stefan; et al. (Blood, 2021)
Chronic graft-versus-host disease (cGVHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGVHD remain poorly understood, and targeted therapies for clinical use are not well established. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGVHD (sclGVHD). WNT signaling was activated in human sclGVHD with increased nuclear accumulation of the transcription factor β-catenin and a WNT-biased gene expression signature in lesional skin. Treatment with the highly selective tankryase inhibitor G007-LK, the CK1α agonist pyrvinium, or the LRP6 inhibitor salinomycin abrogated the activation of WNT signaling and protected against experimental cGVHD, without a significant impact on graft-versus-leukemia effect (GVL). Treatment with G007-LK, pyrvinium, or salinomycin almost completely prevented the development of clinical and histological features in the B10.D2 (H-2d) → BALB/c (H-2d) and LP/J (H-2b) → C57BL/6 (H-2b) models of sclGVHD. Inhibition of canonical WNT signaling reduced the release of extracellular matrix from fibroblasts and reduced leukocyte influx, suggesting that WNT signaling stimulates fibrotic tissue remodeling by direct effects on fibroblasts and by indirect inflammation-dependent effects in sclGVHD. Our findings may have direct translational potential, because pyrvinium is in clinical use, and tankyrase inhibitors are in clinical trials for other indications.
CRIS-Team Scopus Importer:2021-05-28

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy - Zehender, Ariella; Li, Yi-Nan; Lin, Neng Yu; Stefanica, Adrian; Nüchel, Julian; Chen, Chih-Wei; Hsu, Hsiao Han; Zhu, Honglin; Ding, Xiao; Huang, Jingang; Shen, Lichong; Györfi, Andrea-Hermina; et al. (Nature Communications, 2021)
Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16 histone acetyltransferase MYST1, which regulates the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signaling to aberrant autophagy and deregulated epigenetics in fibrotic diseases and may contribute to the development of therapeutic interventions in fibrotic diseases.
CRIS-Team Scopus Importer:2021-08-06

THE NUCLEAR RECEPTOR TR4 ORCHESTRATES CYTOSKELETAL ORGANIZATION IN A G alpha 12/ROCK-DEPENDENT MANNER TO PROMOTE MYOFIBROBLAST DIFFERENTIATION AND TISSUE FIBROSIS IN SYSTEMIC SCLEROSIS - Shen, Lichong; Zhang, Yun; Honglin, Z.; Distler, Jörg (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04